2013
DOI: 10.1155/2013/840964
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Metabolic Syndrome and History of Cervical Cancer among a US National Population

Abstract: The metabolic changes present in the metabolic syndrome (MetS) have been associated with increased risk of pancreatic and colon cancers; however, there is little information about the association between MetS and cervical cancer risk. We performed a case-control study using data from the National Health and Nutrition Examination Survey (NHANES) between 1999–2010. We identified women 21 years of age and older, of which an estimated 585,924 (2.3% of the sample) self-reported a history of cervical cancer (cases).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 52 publications
1
22
1
1
Order By: Relevance
“…The prevalence of HPV was much higher in females compared with males in the presence of MetS. We found that the presence of MetS was positively associated with positive antibodies against HPV 6,11,16,or 18 genotypes. The adjusted association also supported that MetS increases the risk of HPV positivity to a similar extent in both males and females.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The prevalence of HPV was much higher in females compared with males in the presence of MetS. We found that the presence of MetS was positively associated with positive antibodies against HPV 6,11,16,or 18 genotypes. The adjusted association also supported that MetS increases the risk of HPV positivity to a similar extent in both males and females.…”
Section: Discussionmentioning
confidence: 60%
“…We theorize that our findings differ with Liu and colleagues' study due to the different definitions of HPV infection. In our study, HPV positivity was based on serum sample results for genotypes HPV 6,11,16,or 18, whereas Liu and colleagues' study was based on self-collected vaginal swabs with testing for any of the 37 HPV subtypes. In contrast, a more recent prospective study conducted in China among females showed that MetS increases the risk of HPV infection (25).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, insulin deficiency has been linked to defective ovulation, and this can be reversed through treatment with insulin in diabetic rodents. Ovarian protein glycation has been described in non-diabetic mice and hamsters (65) and has the likelihood of affecting ovarian aging in mice (65). These observations are suggestive of the direct harmful effects of hyperglycemia and low insulin levels on ovarian functions, which in turn have a direct impact on women's fertility (66,67).…”
Section: Ovarian Functionmentioning
confidence: 97%
“…On the basis of previous literature, the following were included as covariates in our analyses [24]. Total physical activity level was based on physical activity due to house/yard work, transportation and recreational/leisure-time activities.…”
Section: Covariatesmentioning
confidence: 99%